Financial sector and outbreak of the economic crisis in 2008: IFRS versus US GAAP - Sotirios Rouvolis (Journal of Capital Markets Studies (JCMS), 2022)
Purpose: Testing a total of five hypotheses, the paper contributes to overall comparison of the two regimes, as it scrutinises whether these improvements have helped regulate this sector. Although it appears that, for the first time, International Financial Reporting Standards (IFRS) had a more timely effect than US Generally Accepted Accounting Principles (GAAP), multiple parameters must be taken into consideration. The banking system has additional rules that may affect financial statements, such as the Basel Accord which sets many policies closely related to the IFRS, such as deferred tax credits. In this way, this paper aim to enrich the results of these decisions, and illuminate aspects of amendments to IFRS and US GAAP in light of the crisis. Focussing on the financial sector, the author sought to critically evaluate their reactions, and to question some of their fundamental rules in practice. This is vital for accounting researchers and analysts, allowing for the first time to compare IFRS performance between Europe and the US, and make better investment evaluations. Design/methodology/approach: The study sought to detect whether IFRS and US GAAP protected firms from abnormal sales arising from the outbreak of the crisis, whether the reclassification option under IFRS was an answer to the crisis, and whether IFRS and US GAAP succeeded in regulating shadow banking through their amendments. Therefore, it processes five hypotheses. In order to detect the effects of the crisis on accounting regimes, the analysis focused only on companies from the financial sector composed of the banking industry, insurance companies and shadow banking. The author included firms from Australia, Germany, Greece, the UK and the US, and collected information on 679 financial institutions for the period 2009-2013. The author settled on these time frames because the author aimed to capture IFRS performance surrounding the crisis effects in 2008 and the amendments that followed. In this way, the author applied quantitative methods using only numerical data over a given period. Findings: The results suggest that the reclassification option was successful, helping firms to perform better amid the crisis, indicating that the manipulation of the crisis was appropriate. It seems therefore that US GAAP should have activated this option for US firms. However, the US may not have hurried to act because its banking sector seemed to recover more quickly than in Australia and Europe. Either way, both regimes need to consider speculative market cases that might have appeared during the crisis, as the author have detected cases of abnormal returns. Finally, concerning regulation of the shadow banking sector, the results seem to be encouraging only with regard to the latest improvements and only for all countries examined. Originality/value: The project contributes to debate on the reactions of both IFRS and US GAAP during and after the economic crisis. For this, it addresses several questions to investigate the performance of the financial sector under both regimes, identifying possible additional effects and considerations. More specifically, it answers if the fair value orientation actually contributes to the financial crisis through contagion effects, while it addresses additional questions. Have these two global accounting regimes succeeded in overcoming the consequences of the crisis? Have amendments and the introduction of new standards to IFRS and US GAAP achieved regulation of shadow banking? Which of the two has performed better? As aforementioned, the analysis focused only on companies from the financial sector composed of the banking industry, insurance companies and shadow banking firms from Australia, Germany, Greece, the UK and the US, for the period 2009-2013.
Keywords: 330; IFRS; US GAAP; Earnings management; Financial crisis; Shadow banking